2023
DOI: 10.3390/antiox12030641
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor NRF2 Has Epigenetic Regulatory Functions Modulating HDACs, DNMTs, and miRNA Biogenesis

Abstract: The epigenetic regulation of gene expression is a complex and tightly regulated process that defines cellular identity and is associated with health and disease processes. Oxidative stress is capable of inducing epigenetic modifications. The transcription factor NRF2 (nuclear factor erythroid-derived 2-like 2) is a master regulator of cellular homeostasis, regulating genes bearing antioxidant response elements (AREs) in their promoters. Here, we report the identification of ARE sequences in the promoter region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…The p62/SQSTM1-Keap1-Nrf2 axis is linked to selective autophagy and regulated by post-translational modifications such as sequential phosphorylation and ubiquitination of p62/SQSTM1 (Kageyama et al, 2018). It is known that the transcription factor NRF2 has epigenetic regulatory functions modulating Dnmts and other related enzymes (Silva-Llanes et al, 2023). We recently, showed that inhibiting either Dnmt1 or Dnmt3a caused increased p62 levels in embryos (Uysal et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The p62/SQSTM1-Keap1-Nrf2 axis is linked to selective autophagy and regulated by post-translational modifications such as sequential phosphorylation and ubiquitination of p62/SQSTM1 (Kageyama et al, 2018). It is known that the transcription factor NRF2 has epigenetic regulatory functions modulating Dnmts and other related enzymes (Silva-Llanes et al, 2023). We recently, showed that inhibiting either Dnmt1 or Dnmt3a caused increased p62 levels in embryos (Uysal et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Another degradation mechanism for NRF2 was proposed involving inositol requiring enzyme 1 (IRE1)/E3 ubiquitin ligase synoviolin (HRD1) present in the ER and whose expression is enhanced by activation of the X-box binding protein 1 (XBP1)-HRD1 arm under conditions of reticulum stress [ 30 ] ( Figure 2 ). Finally, indirect regulation may occur through the modulation of miRNAs controlling KEAP1 and CUL3 [ 31 ].…”
Section: Nrf2 As a Sensor Of Cellular Redox Statementioning
confidence: 99%
“…Furthermore, miRNAs capable of regulating NFE2L2 were identified in the context of cancer [ 52 ] and cardiovascular or neurodegenerative diseases [ 53 , 54 ]. Recently, thanks to the analysis of embryonic fibroblasts derived from NRF2-deficient mice, or with the use of activators that modulate the KEAP1 and GSK3 pathways in hippocampal neurons, it was shown that NRF2 can in turn regulate epigenetic mechanisms by controlling the expression of HDAC1 , SIRT1, and DNA (cytosine-5)-methyltransferases ( DNMTs ) that have ARE elements in their promoters [ 31 ]. The modulation of oxidative stress-associated miRNAs (redoximiRs), such as miR-27c-3p, miR-27b-3p, miR-128-3p and miR-155-5p, was also demonstrated [ 55 ].…”
Section: Nrf2 Beyond Its Antioxidant Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the transcription factor NRF2, aging is the main cause of the decline in its activity, since it has been shown that its capacity to induce the expression of antioxidant and detoxifying enzymes decreases with age [ 21 , 22 , 23 ]. Given that NRF2 is a pleiotropic transcription factor involved in the modulation of more than 250 genes associated with biotransformation (which is the alteration of a substance within the body) and detoxification [ 24 , 25 ], redox homeostasis [ 26 , 27 ], lipid and carbohydrate metabolism [ 28 , 29 ], inflammation [ 30 , 31 , 32 , 33 ], epigenetics [ 34 ], autophagy [ 35 , 36 , 37 ], and proteasomes [ 32 , 38 , 39 , 40 ] ( Figure 3 ), which are mechanisms involved in aging, there is clearly an interdependence between aging and NRF2. In this review, we will focus on some of these relevant points, such as genomic instability, loss of proteostasis/autophagy, cellular senescence, stem cell exhaustion, inflammation, and mitochondrial dysfunction.…”
Section: Aging and Its Connection To Nrf2mentioning
confidence: 99%